Pengaruh Pelatihan, Pengalaman Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada UD. Rimang Decoration Grogol Kabupaten Kediri - Fadia Fragita; Moch. Saleh Udin; Trisnia Widuri (STIKes Ibnu Sina Ajibarang, 2023)
This research aims to determine the influence of training variables (X1), work experience (X2), and work environment (X3) on employee performance (Y) at UD Rimang Decoration. This type of research is quantitative research. The data collection techniques used are primary data and secondary data. The sample selection used the saturated sampling method, the number of samples in the study was 35 respondents at UD Rimang Decoration. The analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test and Coefficient of Determination Test. The results of the research obtained the multiple linear regression equation Y= 2.670 + 0.287X1 + 0.383X2 + 0.321X3 and the t test results of the variables training, work experience and work environment had a partially significant effect on employee performance with sig < 0.05. The F test results obtained Fcount results with a significance value of 0.000 < 0.05. From the results of the analysis it can be concluded that training, work experience and work environment have a partially significant effect on the performance of UD Rimang Decoration employees.